2005
DOI: 10.1093/carcin/bgi070
|View full text |Cite
|
Sign up to set email alerts
|

Role of ICAM1 in invasion of human breast cancer cells

Abstract: We identified previously a region on chromosome 19p13.2 spanning the genes encoding the intercellular adhesion molecules (ICAM), ICAM1, ICAM4 and ICAM5 as a breast cancer susceptibility locus. Genetic variants in this region were also associated with indicators of disease severity, including higher rates of metastases to other organs. Based on this association, we set out to explore the role of ICAM1 in proliferation and invasion of human breast cancer cells. We observed that ICAM1 downregulation at the mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(205 citation statements)
references
References 44 publications
11
183
0
5
Order By: Relevance
“…LTA inhibited rhTNF-α-mediated THP-1 cell adhesion to HT-29 Adhesion molecules such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) are implicated in cancer progression (O'Hanlon et al, 2002;Rosette et al, 2005). In this study, the effect of pLTA on the TNF-α-induced expression of adhesion molecules was examined.…”
Section: Rhtnf-α Increased Il-8 Production In Ht-29 Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…LTA inhibited rhTNF-α-mediated THP-1 cell adhesion to HT-29 Adhesion molecules such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) are implicated in cancer progression (O'Hanlon et al, 2002;Rosette et al, 2005). In this study, the effect of pLTA on the TNF-α-induced expression of adhesion molecules was examined.…”
Section: Rhtnf-α Increased Il-8 Production In Ht-29 Cellsmentioning
confidence: 96%
“…TNF-α and nitric oxide (NO) trigger colonic inflammation and carcinogenesis in a Helicobacter hepaticus-infected mouse model, indicating that inflammation mediated by elevated TNF-α and NO causes colon carcinogenesis (Erdman et al, 2009;Kolios et al, 1996). Adhesion molecules, such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1), are also implicated in cancer progression (O'Hanlon et al, 2002;Rosette et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The transwell chambers were incubated at 37°C in 5% CO 2 humidified atmosphere for 48 h. The cells that had not invaded were removed from the upper face of the filters using cotton swabs. The cells that had invaded to the lower surface of the filters were fixed and stained in 0.1% crystal violet (23), and quantified by counting the numbers of cells that penetrated the membrane in five microscopic fields (at ×100 magnification) per filter. The experiment was repeated thrice.…”
Section: In Vitro Cell Invasion Assaymentioning
confidence: 99%
“…ICAM molecules may target and block tumor progression by stimulation of an immune response such as leukocyte activation (15,16). Conversely, other investigations have shown that ICAM molecules are involved in cancer malignancy because their increased expressions are associated with a poor diagnosis, lower survival rates and metastasis in some cancers including melanoma, breast cancer and leukemia (17)(18)(19)(20)(21)(22)(23)(24). We have also reported that an increase of ICAM-3 expression in several cancer cells and specimens of cervical cancer patients induced enhanced radio-resistance by the activation of focal adhesion kinase (FAK) (25) and promoted cancer cell proliferation by the activation of Akt and p44/42 MAPK (26).…”
Section: Introductionmentioning
confidence: 99%